Analysis of the effects of earnings ratio per share, price earnings and return on equity ratio upon the change of shares price at PT. Telekomunikasi Indonesia Tbk years of 2008 - 2017 - Dimas Ari Darmantyo; Shelva Kalay Shelwin (The Management Journal of Binaniaga, 2019)
This research has tested some financial ratios of Earning Per Share, Price Earning Ratio and Return On Equity upon the Change of Shares Price at telecommunication company sector for the period of 2008 to 2017 to know the significance of those ratios, so that, it can be used by the investors to make a decision before investing their money. By having Time Series data of 2008 – 2017, this research has found out that the variables of Earning Per Shares (EPS) and Price Earning Ratio (PER) have significantly affected the change of shares price, but Return On Equity (ROE) has not significantly affected it. This research has indicated that the three independent variables (EPS, PER and ROE) have significantly affected shares price change. Keywords: Finance Ratio, Return On Equity, Earning Per Share, Price Earning Ratio and price of shares